Trends in long-term care prevention research in occupational therapy - Sawada, Yuki (International journal of exercise science, 2020)
[Purpose] In Japan, as part of response measures for its aging population, the national government has been implementing nursing care prevention programs. The Japanese Association of Occupational Therapists clarified the details of skills that can be offered by occupational therapists in nursing care prevention. Therefore, this study aimed to understand the trends in the kind of studies that have been conducted on nursing care prevention in occupational therapy. [Subjects and Methods] This study examined 15 original papers that were published in The Journal of Japanese Occupational Therapy Association during the 10 years up to September 2020 by searching the Japanese research database Ichushi Web using “nursing care prevention” as the keyword. The study investigated which of the following stages of prevention were examined in the 15 papers: primary, secondary, or tertiary prevention. Aspects such as study objectives and details were also examined. [Results] Majority of the studies examined concerned primary prevention. The studies could be divided into the following categories: those that identified indicators that contribute to nursing care prevention and those that evaluated the effect of programs implemented through nursing care prevention workshops. [Conclusion] Studies on nursing care prevention in occupational therapy focus on identifying indicators that can contribute to nursing care prevention. It can be considered that these studies are conducted as a preparatory step for studies examining programs that have been developed from the perspective of occupational therapy as well as the effect of such programs.